Encounters of the children of Abraham from ancient to modern times - Laato, Antti.; Lindqvist, Pekka. (Studies on the Children of Abraham, 2010)
Christianity, Judaism and Islam - the Children of Abraham - constitute the spiritual foundations of Western civilization. They affect the interactions of entire nations and individuals, though their history is often understood as one of conflict and controversy. The present volume documents past encounters and confrontations, though it also shows that the history of the three faiths is not merely one of conflict but also one of co-existence and dialogue. The rich shared theological traditions of the Abrahamic religions provide positive encouragement to present-day meetings between their followers. The book contains 16 contributions by scholars from various fields of religious studies. It should appeal to everyone interested in interreligious encounters.